PERSONAL QUALITIES OF LEARNING FACILITATORS IN ADULT AND CONTINUING EDUCATION : OPINION OF ADULT EDUCATORS IN LATVIA AND LITHUANIA - Zuzevičiūtė, Vaiva; Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper highlights the key findings from a comparative study conducted in 2011- 2012 using the project “Qualified to Teach” − QF2TEACH first wave questionnaire (www.qf2teach.eu). The questionnaire was structured in nine domains: personal qualities; interpersonal behaviour and communication with learners; cooperation with the external environment; planning and management; access and progression of learners; subject-related, specialist domain; monitoring and assessment of learning processes; didacticalmethodological domain; personal development and reflection. In present paper the main results of transnational survey in Latvia and Lithuania are analysed in order to evaluate the importance of certain personal qualities of learning facilitators in adult and continuing education from current and future perspectives as well as to identify the main future-required personal qualities. The study results indicated that open mindedness, optimism, emotional stability, sincerity, pro-activity, flexibility, sociability, tolerance, and morality (ethics) have been named both by the Latvian and Lithuanian adult educators as the main future-required personal qualities of the learning facilitators in adult and continuing education.